On a “grouplike” family of quasigroups - Fares, Ahmed Al; Karaali, Gizem (Examples and counterexamples, 2025)
Quasigroups are algebraic structures in which divisibility is always defined. This paper illustrates some similarities and differences between quasigroup theory and group theory, by singling out a special family of quasigroups which seem to be most “grouplike”. •We illustrate several similarities between quasigroup theory and group theory.•We also illustrate a handful of differences between quasigroup theory and group theory.•We single out a special family of quasigroups which seem to be most “grouplike”.